DETERMINING THE PHYSICAL INDICATORS AND READINESS OF A PERSON - Namozova Munisa Ziyodullo qizi (Journal of new century innovations, 2023)
Abstract. This article highlights the role of Uzbek folk games in the formation of physical qualities in school s pupil , the importance of our youth as a harmonious personality, which is considered as the future of our country.